A segmentation planning method based on the change rate of cross-sectional area of single V-groove for robotic multi-pass welding in intersecting pipe-pipe joint - Zhang, Yang; Lv, Xiaoqing; Xu, Lianyong; Jing, Hongyang; Han, Yongdian (International journal of advanced manufacturing technology, 2019)
In order to meet the demand of robotic multi-pass welding of single V-groove with an uneven and irregular change of intersecting pipes, a novel method in which the weld was divided into several segments according to the change rate of cross-sectional area was put forward in this paper. It was effective to avoid repair welding and secondary processing for such complex joints. By controlling the welding parameters in each segment, the amount of filler metal changed with the cross-sectional area of weld groove; thus, the number of weld passes kept unchanged in each layer and the appearance of the weld remained flat. For each segment, the appropriate welding parameters were identified according to the target value of the size of welding seam through the second-order regression prediction model which was related to the width and height of weld seam. Finally, the feasibility of the welding trajectory was verified by virtual simulation. Welding experiment was carried out and the actual welding seam was basically consistent with the planning results. It was proved that this planning method for sectional welding of the welding seam according to the variation of cross-sectional area is feasible and can be applied to practical welding engineering.